Sistem Pendukung Keputusan Pemilihan Bayi Stunting di Desa Parumasan Kabupaten Pandeglang menggunakan Metode Simple Additive Weighting (SAW) - M Samsul Aripin; I Made Sugi Ardana (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
Stunting remains a major public health issue in Indonesia, including in Parumasan Village, Pandeglang Regency, due to its long-term impacts on children’s growth, cognitive development, and overall health. The determination of stunting status at Puskesmas Cipeucang is still conducted manually through posyandu records and Excel-based recapitulation, which may lead to data inaccuracies and delays in treatment. To address these limitations, this study develops a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method as a structured assessment approach based on multiple health criteria relevant to stunting risk. The SAW method was selected for its ability to perform weighting and data normalization in a simple and accurate manner, making it suitable for implementation by healthcare workers. Data were collected through observations, interviews, and literature reviews. The results show that the SAW-based DSS processes child data more quickly and integratively compared to manual systems, thereby enhancing the effectiveness and efficiency of stunting risk identification. This system is expected to support healthcare workers in making more accurate decisions and contribute to stunting prevention efforts in the Puskesmas Cipeucang area.